2016
DOI: 10.1080/00365513.2016.1233574
|View full text |Cite
|
Sign up to set email alerts
|

Intraabdominal microdialysis – methodological challenges

Abstract: Microdialysis is used for in vivo sampling of extracellular molecules. The technique provides a continuous and dynamic view of concentrations of both endogenous released and exogenous administered substances. Microdialysis carries a low risk of complications and has proven to be a safe procedure in humans. The technique has been applied in several clinical areas, including gastrointestinal surgery. Microdialysis may be used for studies of tissue metabolism, and the technique is also a promising tool for pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
3
5
0
Order By: Relevance
“…Glycerol is derived from lipolysis or the breakdown of phospholipids, for example, in cell membranes, and is considered a marker of tissue hypoxia and/or energy depletion. 25 The subcutaneous glycerol concentrations were numerically much higher than the intraperitoneal concentrations, which corresponds to findings in abdominal surgery and may be explained by the accumulation of glycerol in adipose tissue. 25,26 The intraperitoneal glycerol concentration was unchanged throughout the perioperative course, which is not surprising since the included patients were free from complications.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Glycerol is derived from lipolysis or the breakdown of phospholipids, for example, in cell membranes, and is considered a marker of tissue hypoxia and/or energy depletion. 25 The subcutaneous glycerol concentrations were numerically much higher than the intraperitoneal concentrations, which corresponds to findings in abdominal surgery and may be explained by the accumulation of glycerol in adipose tissue. 25,26 The intraperitoneal glycerol concentration was unchanged throughout the perioperative course, which is not surprising since the included patients were free from complications.…”
Section: Discussionsupporting
confidence: 57%
“…25 The subcutaneous glycerol concentrations were numerically much higher than the intraperitoneal concentrations, which corresponds to findings in abdominal surgery and may be explained by the accumulation of glycerol in adipose tissue. 25,26 The intraperitoneal glycerol concentration was unchanged throughout the perioperative course, which is not surprising since the included patients were free from complications. This finding indicates that the intra-abdominal organs were not severely ischaemic and only reversibly put at risk for damage.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, arterial and hepatic lactate remained low throughout the experiment, and ischemic hyperlactatemia was thus not present, and we consider a severe hypoperfusion unlikely. The use of a high cut-off (100 kDa)-, rather than a 20 kDa-catheter could result in a loss of perfusion fluid and dilution of the sampled metabolites [36], however, we have shown that this can be prevented by using a colloidal perfusion fluid applied in this study [37]. Because of the experimental time frame of 10 h our study lacks information about the later postoperative course.…”
Section: Limitationsmentioning
confidence: 79%